Proposal for a new T-stage classification system for distal cholangiocarcinoma: a 10-institution study from the U.S. Extrahepatic Biliary Malignancy Consortium. Issue 10 (October 2016) - Postlewait, Lauren M.; Ethun, Cecilia G.; Le, Nina; Pawlik, Timothy M.; Buettner, Stefan; Poultsides, George; Tran, Thuy; Idrees, Kamran; Isom, Chelsea A.; Fields, Ryan C.; Krasnick, Bradley; Weber, Sharon M.; et al.
Abstract: Background: Seventh AJCC distal cholangiocarcinoma T-stage classification inadequately separates patients by survival. This retrospective study aimed to define a novel T-stage system to better stratify patients after resection. Methods: Curative-intent pancreaticoduodenectomies for distal cholangiocarcinoma (1/2000-5/2015) at 10 US institutions were included. Relationships between tumor characteristics and overall survival (OS) were assessed and incorporated into a novel T-stage classification. Results: 176 patients (median follow-up: 24mo) were included. Current AJCC T-stage was not associated with OS (T1: 23mo, T2: 20mo, T3: 25mo, T4: 12mo; p = 0.355). Tumor size ≥3 cm and presence of lymphovascular invasion (LVI) were associated with decreased OS on univariate and multivariable analyses. Patients were stratified into 3 groups [T1: size <3 cm and (−)LVI (n = 69; 39.2%); T2: size ≥3 cm and (−)LVI or size <3 cm and (+)LVI (n = 82; 46.6%); and T3: size ≥3 cm and (+)LVI (n = 25; 14.2%)]. Each progressive proposed T-stage was associated with decreased median OS (T1: 35mo; T2: 20mo; T3: 8mo; p = 0.002). Conclusion: Current AJCC distal cholangiocarcinoma T-stage does not adequately stratify patients by survival. This proposed T-stage classification, based on tumor size and LVI, better differentiates patient outcomes after resection and could be considered for incorporation into the next AJCC distal cholangiocarcinoma staging system.